Demonstration of the Rationale for Therapeutic Drug Monitoring of Isavuconazole: A Case Report with a Lung Transplant Recipient - Dvořáčková, Eliška; Zajacová, Andrea; Havlín, Jan; Klapková, Eva; Lischke, Robert; Slanař, Ondřej; Šíma, Martin (Prague medical report, 2023)
Mucormycosis is a rare invasive fungal disease diagnosed in immunocompromised patients, including those with diabetes or iron overload, and in patients treated for hematological malignancies or after transplantation. Isavuconazole is a triazole antifungal effective against Mucorales with good tolerability, but with potential for relatively high interindividual variability in pharmacokinetics. This report demonstrates the case of a lung transplant recipient treated with isavuconasole that exhibits a very long elimination half-life of 159 hours, and discusses the practical implications of this finding for dosage adjustment and need for therapeutic drug monitoring.
Keywords: plíce; Antifungals; Triazoles; Therapeutic drug monitoring; Isavuconazole; Humans; monitorování léčiv; Transplant Recipients; Lung transplant recipient; aspergilóza; mukormykóza; Lung; Aspergillosis; Drug Monitoring; příjemce transplantátu; Mucormycosis; lidé; triazoly; Pharmacokinetics